Sociodemographic Factors Are Predictors of Poorer Clinical Outcome Trajectories in Early Rheumatoid Arthritis: Results from the Singapore Early Arthritis Cohort - Zou, Yuhan (2019)
ACR (Americal College of Rheumatology) meeting